Eccrine poroma - Gurman Singh Bhasin; Swapna S Khatu; Nitin Chaudhari (Wolters Kluwer Medknow Publications, 2023)
Poromas designate a group of benign adnexal neoplasms with poroid (terminal duct) differentiation. The great majority of these lesions are found on the palms and soles and present as moist exophytic lesions. Herein we report a patient who presented with a slow growing nodular lesion over the left palm which was later histopathologically confirmed to be case of Eccrine Poroma.